Case Report: Postacute Rehabilitation of Guillain-Barré Syndrome and Cerebral Vasculitis-Like Pattern Accompanied by SARS-CoV-2 Infection - Colonna, Stefano; Sciumé, Luciana; Giarda, Federico; Innocenti, Alessandro; Beretta, Giovanna; Dalla Costa, Davide (Frontiers in Neurology, 2021)
Introduction: The main clinical manifestation of the novel Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is respiratory issues. Neurological manifestations are being increasingly recognized, including febrile seizures, headache, dizziness, and myalgia, as well as encephalopathy, encephalitis, stroke, and acute peripheral nerve diseases. Cerebral vasculitis is rarely reported. We describe a case of SARS-CoV-2 interstitial pneumonia complicated by flaccid tetraplegia due to Guillain-Barré Syndrome (GBS) associated with a cerebral vasculitis-like pattern. Case description: A 62-year-old man was hospitalized for cough, fever, and severe respiratory failure requiring tracheal intubation and invasive ventilation. The chest Computerized Tomography (CT) showed images related to interstitial pneumonia and the subsequent nasopharyngeal swab confirmed the presence of SARS-CoV-2 infection. During the hospitalization, there was a progressive deterioration of the senses associated with areflexic flaccid tetraplegia. The treatment with high doses of immunoglobulin G (IgG) led to the immediate improvement of the general conditions and a partial response in terms of recovery of the upper limb and of the distal lower limb movements. Subsequently the patient was admitted to our Rehabilitation Unit, where he received an intensive rehabilitation treatment consisting of physiotherapy and occupational therapy. Two months later the patient was discharged at home and able to walk independently even for long distances thanks to the use of Ankle-Foot Orthosis (AFO). Conclusion: In this report, we present the case of a patient with peripheral and central neurological damage occurred later severe pneumonia induced by SARS-CoV-2. The Immunoglobulin G therapy allowed the patient to benefit considerably from early rehabilitation, reaching the walking, increasing the independence in daily living tasks, and enabling safe discharge from hospital to home. Related neurologic complications of SARS-CoV-2 infection suffer a lack of understanding and further investigations should be conducted.